Vestibular Schwannoma Excision in Sporadic versus Neurofibromatosis Type 2 Populations. (November 2015) - Mahboubi, Hossein; Maducdoc, Marlon M.; Yau, Amy Y.; Ziai, Kasra; Ghavami, Yaser; Badran, Karam W.; Al-Thobaiti, Majid; Brandon, Bryan; Djalilian, Hamid R.
Objective: To understand the differences in characteristics of neurofibromatosis type 2 (NF2) and sporadic patients with surgically excised vestibular schwannomas in the state of California. Study Design: Cross-sectional. Setting, Subjects, and Methods: The records of all patients who underwent vestibular schwannoma excision between 1997 and 2011 were extracted from the California Hospital Inpatient Discharge Databases (CHIDD). NF2 cases were identified using ICD-9-CM diagnosis code 237.72, neurofibromatosis, type 2. All other cases were recoded as sporadic. Trends in total number and population-adjusted rates (per 1 million California residents) of surgery, demographics, hospital case volume, state of residency, complications, length of stay, total charges, expected source of payment, and disposition were examined. Results: Vestibular schwannoma (VS) excision was performed on 7017 patients, of which 464 patients (6.6%) had NF2. The population-adjusted surgery rate declined from 11.8 to 6.2 ( P < .001) for sporadic cases and from 0.3 to 0.2 ( P = .01) for NF2 cases over the study period. NF2 was associated with younger age (mean, 32.9 vs 51.3), higher rate of other complications (8.8% vs 4.4%) and facial nerve complications (32.3% vs 16.8%), higher total charges (median $70, 106 vs $46, 395), longer stay (median 5 vs 4), and high volume hospitals (80.4% vs 48.8%) (all P < .001). Conclusion: The surgery rates for vestibular schwannoma excision for both sporadic and NF2 patients have declined, but the decline is more prominent for sporadic cases. NF2 patients tend to be younger and have a longer hospitalization and possibly higher corresponding hospital charges compared to patients with sporadic VS.